Experimental Study on the Flow Condensation Heat Transfer of R290 and R22 in a Horizontal Circular Minitube - Xiao Hang; Li Junming (Zhileng xuebao)
The condensation heat transfer characteristics of R290 and R22 were investigated experimentally in a horizontal circular minitube with 1.085 mm diameter. The mass flow rate of R22 is 200-1200 kg/(m2?s), and that of R290 is 200-650 kg/(m2?s). The saturation temperature is 40 ℃ and 50 ℃ respectively during the experiment. The experimental results show that at the higher mass flow rate of R22, the condensation heat transfer coefficient increases slowly or even decreases little with the vapor quality increasing, for the R290 at a less mass flow rate, the heat transfer coefficient will decreases slightly at a low vapor quality. The condensation heat transfer coefficient of R290 is higher than that of the R22 at the same experimental conditions. The experimental results are also compared with some of the existing correlations, which shows that the Wang et al.(2002) correlation predicts the experimental data of R290 very well ,with an overall mean absolute error of 17.5%, while Kim et al. (2013) correlation makes the best prediction to the R22’s data, with an overall mean absolute error of 18.4%.